Measurement of beauty production via non-prompt charm hadrons in p–Pb collisions at s NN $$ \sqrt{s_{NN}} $$ = 5.02 TeV - The ALICE collaboration; S. Acharya; D. Adamová; A. Agarwal; G. Aglieri Rinella; L. Aglietta; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; et al. (Journal of High Energy Physics)
Abstract The production cross sections of D0, D+, and Λ c + $$ Λ_{c}^{+} $$ hadrons originating from beauty-hadron decays (i.e. non-prompt) were measured for the first time at midrapidity in proton–lead (p–Pb) collisions at the center-of-mass energy per nucleon pair of s NN $$ \sqrt{s_{NN}} $$ = 5.02 TeV. Nuclear modification factors (R pPb) of non-prompt D0, D+, and Λ c + $$ Λ_{c}^{+} $$ are calculated as a function of the transverse momentum (p T) to investigate the modification of the momentum spectra measured in p–Pb collisions with respect to those measured in proton–proton (pp) collisions at the same energy. The R pPb measurements are compatible with unity and with the measurements in the prompt charm sector, and do not show a significant p T dependence. The p T-integrated cross sections and p T-integrated R pPb of non-prompt D0 and D+ mesons are also computed by extrapolating the visible cross sections down to p T = 0. The non-prompt D-meson R pPb integrated over p T is compatible with unity and with model calculations implementing modification of the parton distribution functions of nucleons bound in nuclei with respect to free nucleons. The non-prompt Λ c + $$ Λ_{c}^{+} $$ /D0 and D+ /D0 production ratios are computed to investigate hadronisation mechanisms of beauty quarks into mesons and baryons. The measured ratios as a function of p T display a similar trend to that measured for charm hadrons in the same collision system.